Expert system in determining baby disease using web mobile-based weighted product method - Muslihudin M.; Devika G.; Manickam P.; Shankar K.; Putra D.P.; Putra E.P.S.; Huda M.; Hashim W.; Denisova O.P.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Based on the health minister of the republic of Indonesia the number of infant deaths have been decreased from 33,278 in 2015 to 32,007 in 2016 and in 2017 as many as 10,294 cases. This study was conducted to determine the type of disease suffered through the symptoms observed using weighted product method. The weighted method was chosen because it was able to determine the disease of the alternatives. The function of this method is to determine the weight value of each alternative and predetermined disease criteria. There are 7 criteria used in this research are: (1) Crying Excessively, (2)Fever, (3)Diarrhea, (4)Skin Problem, (5)Weight Gain, (6)Height Growth (7)Communication Growth. In addition to criteria also used the criteria weighting value to determine the disease of alternative calculations obtained the largest value contained there at with a value of 0.123, which means that baby 9 is a baby who suffers from many diseases. BEIESP.